Automated Precision Paper Counting with Seamless Data Transmission: Penghitungan Kertas Presisi Otomatis dengan Transmisi Data Tanpa Batas - Letlora, Sutasoma Anggoro; Syahrorini, Syamsudduha (Universitas Muhammadiyah Sidoarjo, 2024)
The integration of automation in the printing industry has revolutionized processes, yet manual calculations persist in centers like Aslaka, managed by Electrical Engineering Laboratory Assistants, leading to inaccuracies and opacity in pricing. This study aims to address this gap by developing an automated pricing device, ensuring precision and transparency in paper quantity and total cost determination. Utilizing research and development methodology, comprehensive testing of IR sensors and IoT-based data transmission was conducted to guarantee reliability. Findings demonstrate successful paper detection by IR sensors at 2 cm and 3 cm distances, with sensor readings accurately displayed on a 20x4 I2C LCD screen. Data transmission to Google Sheets via Pushingbox API exhibited exceptional accuracy, achieving consistent 100% matching. This innovation enhances efficiency and transparency in pricing, offering significant implications for the printing industry's advancement. Highlight: Development Method: Utilizes research and development for comprehensive testing and reliability. Sensor Precision: IR sensors accurately detect paper at varying distances. Data Transmission: IoT enables seamless data transfer to Google Sheets. Keywoard: Automation, Printing Industry, IR Sensors, Transparent Pricing, IoT